The Role of the Sharing Economy and Artificial Intelligence in Health Care: Opportunities and Challenges - Wu, Huailiang; Chan, Nga-Kwo; Zhang, Casper J P; Ming, Wai-Kit (Journal of medical Internet research, 2019)
Health care systems worldwide have been influenced by the globally growing trend toward a sharing economy and will likely advance with these trends in the near future. Therefore, based on peer-to-peer relationships between individuals, sharing health care works by renting medical staff, facilities, and other medical resources. Medical data innovation, integration, analysis, and sharing have the potential to dramatically change the current pattern of the health care system and to provide precise and predictive medical assessment for individuals in the future. In addition, artificial intelligence could be useful in the fields of both clinical medicine and medical research and help to minimize the scarcity of human resources and broaden the role of humans in health care.